Musica getutscht: A Treatise on Musical Instruments by Sebastian Virdung - Bullard, Beth; Bullard, Beth (Cambridge Cambridge University Press, 1993)
Musica getutscht (Basel, 1511) is the earliest printed treatise on musical instruments in the West. Written by a priest and chapel singer named Sebastian Virdung, it provided rudimentary instruction on playing three instruments: the clavichord, the lute and the recorder. This early 'do-it-yourself' manual of instruction not only tells us about music-making in that era, it also illumines other aspects of society in the years just before the Reformation. Its author communicates in a popular style, choosing a mixture of media: a written text in the guise of an informal conversation, coupled with woodcut illustrations and visual aids. Enthusiasts of early music and its performance as well as historians of art, society and the German language will welcome Beth Bullard's substantial introduction and annotations, which help explain the text of this important work and its place in intellectual history.
Modern English edition of Virdung's Musica getutscht (1511)
Keywords: 16th Century (1501-1600); Organology